Phylogenetic position of Javan banteng (Bos javanicus javanicus) from conservation area in Java base on mtDNA analysis - Maryatul Qiptiyah; Satyawan Pudyatmoko; AYPBC Widyatmoko; ILG NURTJAHJANINGSIH; MUHAMMAD ALI IMRON (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Qiptiyah M, Pudyatmoko S, Widyatmoko AYPBC, Nurtjahjaningsih ILG, Imron MA. 2019. Phylogenetic position of Javan banteng (Bos javanicus javanicus) from conservation area in Java base on mtDNA analysis. Biodiversitas 20: 3352-3357. Two of three subspecies of banteng (B. javanicus) can be found in Indonesia, namely B. j. lowi and B. j. javanicus. The taxonomic assignment of the two subspecies is still in the discussion researchers currently. One of the reproductive characters of members the Bovidae family, including the banteng, is known to have interbreeding ability between species and can produce fertile offspring. In some places, there exist grazing cattle near or in the banteng’s natural habitat. This phenomenon aimed to provide banteng mates with cows, which later they will breed high-quality offsprings. Regarding interbreeding capability, this condition can be a threat to the genetic purity of wild banteng. The main objectives of this study were to identify the phylogenetic position of Javan banteng from conservation areas in Java in relation to the other taxon and detect their genetic purity. We analyzed 28 cytochrome b and d-loop region sequences of Javan banteng from feces materials of four conservation areas (Ujung Kulon National Park, Alas Purwo National Park, Meru Betiri National Park, and Baluran National Park). We compared our data with reference sequences data of the other Bovidae species and Capra hircus as outgroup. The reference data was taken from NCBI, and they were analyzed using maximum likelihood. The results showed that Javan banteng was in a different group from other taxa. Separation of subspecies B. j. javanicus and B. j. lowi occurred circa 1.25 mya. The results from this study suggested that there is no indication of genetic introgression between Javan banteng and the (domesticated) cattle.